Cost of Funds Deregulation on Agricultural Investments in Nigeria: An Analysis - Asuquo, Innocent; Arigor, Arigor John; Eyo, Emmanuel Okon (International Journal of Economics and Financial Issues, 2021)
The study examined agricultural investments in the light of deregulating the cost of funds. Factors that determine aggregate credit volume to the sector within the costs of funds regulated and deregulated periods and; the growth level in agricultural credit within the deregulated period were the specific objectives. Secondary data were used, sourced from Central Bank of Nigeria (CBN) and the National Bureau of Statistics (NBS). Data were analyzed using Co-integration technique and Real Credit Growth Rate Model. The Co-integration results showed that in the long-run, average interest lending rate and budgetary allocation were key variables on aggregate credit volume to agricultural sector. In the short-run, savings mobilized by financial institutions, the average lending rate, previous year’s average saving rate, inflation rate and government budgetary allocation to the sector were the significant variables on credit volume to agriculture. The result of the real credit growth rate within the deregulated period was 8.91%. Arising from this, therefore, the study recommended a complete unbundling of the markets as it will ensure funds availability for investments in the sector. Keywords: Agricultural investments, cost of funds, deregulation, Nigeria. JEL Classifications: G11, Q14 DOI: https://doi.org/10.32479/ijefi.8922